Kecemasan Menghadapi Pertandingan Pada Atlet Futsal - Dharmawan, Dimas Cesar, Dra. Partini, M.Si (2016)
Anxiety in the middle of the game is experienced by almost every athlete, as well as futsal athletes. Too much anxiety will affect an athlete to get excessive fear in every game. The purpose of this research is to understand and to know the futsal athlete's anxiety in a game. This research is using interview and observation for collecting data. Informants in this research are futsal athletes who got high anxiety and selected by survey of the futsal athletes in Surakarta. The results of this research showed that anxiety of futsal athletes happened because the opponents of the match is stronger or have a higher rank, the number of spectators and the fear of losing in the match. Some efforts to overcome anxiety from ourselves are; athletes relaxation and therapy in order to distract anxiety. Meanwhile, family, friends and people around can be an external technique to overcome anxiety. The role of motivation from the coach can reduce the anxiety of the futsal athletes.